Exercise prescription as medicine - George K. Lui (Elsevier, 2021)
Exercise has significant benefits to the physical and mental health of adult congenital heart disease (ACHD) patients. Supported Exercise Programme for Adults with Congenital Heart Disease (SEA Change), is a prospective study that enrolled ACHD patients into an exercise training program and demonstrated improvements in both exercise capacity and psychological measurements. As ACHD clinicians provide advice on medical and surgical interventions of their congenital heart condition, exercise is one more prescription in the holistic care of our ACHD patients.